ANALYSIS OF THE ACHIEVEMENT OF QUALITY EDUCATION PRACTICUM IN MECHANICAL ENGINEERING STUDY PROGRAM FKIP PALANGKA RAYA UNIVERSITY - Wiyogo (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
Laboratarium role in engineering education is very important because it provides the experience and deepen skills. So important is the role of laboratarium, then should the quality of practical implementation needs to be addressed is important. The results of the study in quadrant A shows respondents provide an important assessment of the factors availability of tools / materials practice, with a compliance rate of 45.7%. X value of 2.368 indicates the performance level is still low, indicating preparation lab still has not maximized. Y value obtained for 5,179 respondents indicated considers the need for the availability of tools / materials practice is needed. In quadrant B, factor correspondence between education and training to learning courses have X and Y values of 3.768 and 5.379 that indicates the level of performance has a good category and importance, with higher kesusaiannya 70.1%. Factors skills of lecturers / laboratory demonstrates the use of having 73.4% concordance rate. Both of these factors need to be maintained.